2020
DOI: 10.4314/ijs.v21i3.15
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of heteroleptic metal complexes of Isoniazid and Metformin

Abstract: Mixed ligand complexes of Metformin and Isoniazid have been synthesized and characterized by solubility studies, percentage metal analysis, UV-Vis spectroscopy, IR spectroscopy, magnetic moments and conductivity measurements. The infrared spectra revealed the coordination of the ligands to the metal ions [manganese(II), cobalt(II), nickel(II), copper(II) and zinc(II)]. Meformin coordinated as a bidentate ligand via the imine nitrogen while isoniazid coordinated through its amino nitrogen (NH) and carbonyl oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The syntheses and structural elucidations of several mixed ligand complexes of nicotinamide have also been reported (Sahin et al, 2016;Cakir et al, 2001;Ucar et al, 2007, Kose , 2007Al-noor, 2007, Yurdakul et al, 2014. Studies on the antimicrobial activities of the mixed ligand complexes of nicotinamide have shown that the complexes possess higher activity than the free ligands, which is in agreement with numerous reports that have shown that metal complexes of ligands or organic drugs are more active than the free ligands or drugs (Lawal et al, 2015;Akinyele et al, 2020 recorded in the 4000 -400 cm region with a Shimadzu FT-IR 8000 spectrophotometer using KBr pellets. UV-Visible spectra of the samples were measured in the range 800 -200 nm using a Shimadzu UV-Vis 1800 spectrophotometer.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…The syntheses and structural elucidations of several mixed ligand complexes of nicotinamide have also been reported (Sahin et al, 2016;Cakir et al, 2001;Ucar et al, 2007, Kose , 2007Al-noor, 2007, Yurdakul et al, 2014. Studies on the antimicrobial activities of the mixed ligand complexes of nicotinamide have shown that the complexes possess higher activity than the free ligands, which is in agreement with numerous reports that have shown that metal complexes of ligands or organic drugs are more active than the free ligands or drugs (Lawal et al, 2015;Akinyele et al, 2020 recorded in the 4000 -400 cm region with a Shimadzu FT-IR 8000 spectrophotometer using KBr pellets. UV-Visible spectra of the samples were measured in the range 800 -200 nm using a Shimadzu UV-Vis 1800 spectrophotometer.…”
Section: Introductionsupporting
confidence: 76%
“…The magnetic moment values as displayed in Table 4, shows that all the complexes are paramagnetic, except the Zn(II) complex which was diamagnetic. The copper(II) complex gave a value of 1.5 BM w h i c h i n d i c a t e s t h e p r e s e n c e o f antiferromagnetism , Akinyele, 2020. The magnetic susceptibility values for cobalt(II) and Ni(II) complexes supports an octahedral geometry (Cotton and Wilkinson, 1966;Lee, 1996).…”
Section: Magnetic Momentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mainly prescribed for type 2 diabetes, but it is also being used to cure polycystic ovarian syndrome, which can lead to infertility and obesity. 1 Unexpectedly, several retrospective epidemiologic studies of diabetic patients consuming metformin or phenformin over extended periods of time found that these medications decreased the risk of cardiovascular diseases and cancer. 2 Overall, metformin's antidiabetic and anticancer modes of action are quite complicated and have been extensively discussed elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have demonstrated that metal complexes of isoniazid, in which isoniazid acts as a mono-, bi-, or poly-dentate ligand, not only have antibacterial activities but also have fascinating biological features. Similarly, these compounds are more effective and less harmful to the liver than isoniazid [18][19]. Multiple studies have highlighted the significance of creating new isoniazid hydrazones as possible antituberculous drugs.…”
Section: Introductionmentioning
confidence: 99%